Enhancing Literacy in Sharia Disaster Insurance Practices in Indonesia - Ellectrananda Anugerah Ash-shidiqqi; Maranatha Lisatyaningrung Hainekam Fobia (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
Reducing losses from natural disasters is an essential component of effective recovery and resilience building. Recognizing this, the Indonesian government has allocated a dedicated budget for disaster management through the State Budget (APBN) and Regional Budget (APBD), as stipulated in Law No. 24 of 2007 concerning Disaster Management. This allocation aims to ensure that resources are available for immediate response and long-term recovery efforts. However, the increasing frequency and severity of natural disasters, exacerbated by climate change, underscore the need for more substantial and adaptive financial mechanisms to address the growing demands for catastrophe funding.Funding mechanisms must extend beyond immediate needs such as emergency response and recovery. They should also encompass disaster risk transfer and mitigation initiatives, which include preventive measures, community preparedness, and investments in rehabilitation and reconstruction. Such an integrated approach not only addresses the consequences of disasters but also reduces risks and vulnerabilities over time.Individual risk insurers play a pivotal role in this framework by providing insurance solutions to help manage potential losses. In this context, the agreement between the insured and the insurer is formalized through a policy. This policy defines the insurer's obligation to cover specific risks that the insured may face in the future, in exchange for regular payments known as premiums. This system of risk transfer is a vital component of a comprehensive disaster risk management strategy, enabling both individuals and institutions to recover more swiftly from the financial impacts of disasters.